Money and Credit in a Keynesian Model of Income Determination - Wynne Godley (Levy Economics Institute of Bard College, 1998)
This paper formally integrates the theory of money and credit derived ultimately from Wicksell into the Keynesian theory of income determination, with assets allocated according to Tobinesque principles. The model deployed has much in common with the modern "endogenous money" school initiated by Kaldor which emphasizes the essential role played by credit in any real life economy, since production takes time and the future is always uncertain. New ground is broken methodologically because all the propositions are justified by simulations of a rigorous (60-equation) model, making it possible to pin down exactly why the results come out as they do. One conclusion of the paper is that there is no such thing as a supply of money distinct from the money which agents wish to hold or find themselves holding. This finding is inimical, possibly in the end lethal, to the way macroeconomics is currently taught as well as to the neoclassical paradigm itself.
Keywords: 330